Prevalence of Atrial Fibrillation in patients attending emergency department of Shahid Gangalal National Heart Centre, Kathmandu, Nepal
Background and Aims: Atrial fibrillation (AF) is the most common sustained arrhythmia. This study aims to evaluate its prevalence in patients attending emergency department of tertiary care cardiac centre. Methods: It was a prospective observational study of 1012 consecutive patients who attended emergency department of Shahid Gangalal National Heart Centre from September 2014 to November 2014. Electrocardiogram, demographic features, diagnosis and clinical presentations were reviewed. Results: Among the 1012 patients, 553 (54.6%) were male and 459(45.4%) were female. Mean age was 52.13